A randomised controlled trial of adjunctive yoga and adjunctive physical exercise training for cognitive dysfunction in schizophrenia. Issue 2 (12th August 2016) - Bhatia, Triptish; Mazumdar, Sati; Wood, Joel; He, Fanyin; Gur, Raquel E.; Gur, Ruben C.; Nimgaonkar, Vishwajit L.; Deshpande, Smita N.
Abstract : Background: Yoga and physical exercise have been used as adjunctive intervention for cognitive dysfunction in schizophrenia (SZ), but controlled comparisons are lacking. Aims: A single-blind randomised controlled trial was designed to evaluate whether yoga training or physical exercise training enhance cognitive functions in SZ, based on a prior pilot study. Methods: Consenting, clinically stable, adult outpatients with SZ ( n =286) completed baseline assessments and were randomised to treatment as usual (TAU), supervised yoga training with TAU (YT) or supervised physical exercise training with TAU (PE). Based on the pilot study, the primary outcome measure was speed index for the cognitive domain of 'attention' in the Penn computerised neurocognitive battery. Using mixed models and contrasts, cognitive functions at baseline, 21 days (end of training), 3 and 6 months post-training were evaluated with intention-to-treat paradigm. Results: Speed index of attention domain in the YT group showed greater improvement than PE at 6 months follow-up ( p <0.036, effect size 0.51). In the PE group, 'accuracy index of attention domain showed greater improvement than TAU alone at 6-month follow-up ( p <0.025, effect size 0.61). For several other cognitive domains, significant improvements were observed with YT or PE compared with TAU alone ( p <0.05, effect sizes 0.30–1.97). Conclusions: Both YT and PE improved attention and additional cognitive domains well past the training period, supporting our prior reported beneficial effect of YT on speed index of attention domain. As adjuncts, YT or PE can benefit individuals with SZ.